Does the Principle of Running a Business in Conventional Vs Sharia Become Differentiator? Study on Banking Industry in Indonesia 2009 - 2014 - Ahmad Adriansyah; Fathoni Zoebaedi; Ramzi A. Zuhdi (Indonesia Banking School, 2016)
Comparing to conventional bank, Islamic banking industry in Indonesia relatively still in the early development stage. Islamic bank is different with conventional bank, and therefore there is a special regulation for Islamic bank. Research conducted in 22 countries (including Indonesia), shows that Islamic banking and has differences with conventional banking in term of business orientation, efficiency, asset kuality and stability. But other research 13 countries (not including Indonesia), show that Islamic banking’s performance is lower than conventional banking (Ariss, 2010). Islamic banking in Indonesia has a unique characteristic. Most of Islamic banking in Indonesia is converted from conventional bank, owned by conventional bank or originated from a conventional bank. Some resource of Islamic bank comes from conventional banking even some of them still using resource from their conventional bank as their parent. This result raises a question, whether in the context of Islamic banking in Indonesia, its performance is significantly different from conventional banks. To answer the research questions above, we do a t-test on ROA and ROE Islamic banks and conventional banks from 2009-2014. The results showed that there was no significant difference between the financial performances of Islamic banks with conventional banks, except for 2014. In 2014 Islamic bank’s ROE is lower than conventional banks. This research opens the opportunity to study the factors that could cause a difference in the performance of Islamic banks vs conventional banks.